Molecular Analysis of 6-pyruvoyltetrahydropterin Synthase Gene in Atypical Phenylketonuric Egyptian Patients - Ahmed, F. Mohamed; Eman, M. Abd Allah; Ahmed, E. Moselhim; Radwa, Gamal; Magdy, M. Mahmoud; Osama, K. Zaki (Journal of Biotechnology and Biomedical Science, 2020)
Background Hyperphenylalaninemia (HPA) combined with neurological signs due to impaired catecholamine, dopamine and serotonin synthesis. Symptoms may appears in first week of life but most seen in age of 4 months. Atypical PKU disease caused mainly by deficiency in 6-pyruvoyltetrahydropterin synthase (PTPS) involved in synthesis of BH4. Clinical symptoms may include poor sucking, impaired tone, ataxia, and seizures. The purpose of this study was to analyze the genotype-phenotype relation among BH4 deficient patients because of PTPS mutations in different state of Egypt. Methods Suspected PKU patients loaded with phenylalanine/Kuvan, and the level of phe and phe/tyrosine ratio determined using tandem mass spectrometry by dried blood spots. Blood samples of 13 unrelated Egyptian patients were collected for total RNA extraction, amplification of PTPS gene by PCR followed with sequencing by Sanger method and finally mutations were recorded for genetic analysis. Results The mean value of phe in 13 patients decreased after loaded of phenylalanine from 482.5μmol/L to 270.63 μmol/L as well as phe/tyrosine ratio was decreased from 13.4 to 6.36 after 24hour of treatment with Kuvan. Sanger sequencing of PTPS gene of those patient showed 21 SNPs and Indels mutations. The most repeated mutation is a novel 23 base pair homozygous deletion in 12/13; c.200C>T in four patients, a novel c.86A>T in two patients and three different mutations located once in three different patients (novel c.22C>T; novel c.273G>A and 405T>C) among patients. On amino acid predicted sequences 4 different types of mutations on protein level were presented, 1 deletion mutation in seven amino acid and 3 different missense mutations in addition to 2 silent mutations among 13 patients. Conclusion Patients were the first case of clinical diagnosis as hyperphenylalaninemia (HPA) undergoing genetic diagnosis for PTPS deficiency in Egypt. The sever HPA patients with severe nervous system damage mainly accompanied with deletion mutations and should pay more attention to the BH4 deficiency. While mild HPA is associated with base substitution mutations with mainly transition mutations (7/9; 78%). Next-generation sequencing technique can increase the mutation detection rate when the hereditary diseases are highly suspected in clinic.
Keywords: HPA: hyperphenylalaninemia; PAH: phenylalanine hydroxylase; Phe: phenylalanine; PKU: phenylketonuria; PTPS: 6-pyruvoyl-tetrahydropterin synthase; BH4: tetrahydrobiopterin